AGE-SPECIFIC CHANGES IN THE INDICATORS OF PHYSICAL DEVELOPMENT OF PRESCHOOL CHILDREN (Conferencea, 2023)
The proverb shows about the physical development of preschool children and the development of physical qualities through exercise